Solidaritas Orang Tulehu dan Orang Buton di Negeri Tulehu - Jouverd Fendli Frans; Elsina Titaley; Pieter Hendra Manuputty (Universitas Muhammadiyah Sorong, 2026)
The people in the Land of Tulehu are a society characterized by a homogeneous society in the Orang Tulehu community, but in the social development of the community until this decade, the existence of the Buton People in the lordship or rights of the Orang Tulehu territory cannot be denied to have existed and settled together in a common settlement area. In this social reality, the social process through social interaction occurs between these two communities and ultimately forms social cohesion that is strengthened by common social solidarity in the environment and areas of common social life. The creation of social cohesion and solidarity between two people with different socio-cultural lives since the arrival of the Buton people to the land of the Tulehu people, gives an idea of the social reality, that there is good solidarity between the two, and in the end does not cause conflicts or social friction between the Tulehu people and the Buton people. Based on the conditions and situations described by the Tulehu and Buton people, this study shows that the Tulehu and Buton people are able to maintain the social solidarity that has been created for so long from their ancestors by building cooperative relations between others, and even open to accepting inter-ethnic marriages, which ultimately creates social cohesion and sustainable social solidarity.